Beyond environmental comfort - Ong, Boon Lay (London : Routledge, 2013)
'Although thermal comfort is the main topic of this book, the sense of comfort is so integral to our general sense of well-being and how we experience buildings that research in this field has expanded to address that larger picture. As such, experts from different fields have contributed in their own respective ways to the overall understanding of the subject. This is the first time that these diverse views have been brought together and additionally, an attempt is made to define the field for the future'--
Includes bibliographical references and index.
Keywords: Architecture -- Human factors; Human comfort